Molecular Response to High Hydrostatic Pressure: Time-Series Transcriptomic Analysis of Shallow-Water Sea Cucumber Apostichopus japonicus - Chen, Jiawei; Liang, Linying; Li, Yanan; Zhang, Haibin (Frontiers in Genetics, 2020)
Hydrostatic pressure is a key environmental factor constraining the benthic migration of shallow-water invertebrates. Although many studies have examined the physiological effects of high hydrostatic pressure on shallow-water invertebrates, the molecular response to high pressure is not fully understood. This question has received increasing attention because ocean warming is forcing the bathymetric migrations of shallow-water invertebrates. Here, we applied time-series transcriptomic analysis to high-pressure incubated and atmospheric pressure-recovered shallow-water sea cucumber (Apostichopus japonicus) to address this question. A total of 44 samples from 15 experimental groups were sequenced. Our results showed that most genes responded to pressure stress at the beginning when pressure was changed, but significant differences of gene expression appeared after 4–6 h. Transcription was the most sensitive biological process responding to high-pressure exposure, which was enriched among up-regulated genes after 2 h, followed by ubiquitination (4 h), endocytosis (6 h), stress response (6 h), methylation regulation (24 h), and transmembrane transportation (24 h). After high-pressure incubation, all these biological processes remained up-regulated within 4–6 h at atmospheric pressure. Overall, our results revealed the dynamic transcriptional response of A. japonicus to high-pressure exposure. Additionally, few quantitative or functional responses related to A. japonicus on transcriptional level was introduced by hydrostatic pressure changes after 1 h and main biological responses were introduced after 4 h, suggesting that, when hydrostatic pressure is the mainly changed environmental factor, it will be better to fix sea cucumber samples for transcriptomic analysis within 1 h, but 4 h will be also acceptable.